Analisis Kepuasan Masyarakat terhadap Pelayanan Pencatatan Pernikahan melalui Sistem Informasi Manajemen Nikah (SIMKAH) - Setianingsih, Purwati; Purwanto, Purwanto; Syarifah, Laili (Pascasarjana STIE Amkop Makassar, 2024)
This research was motivated by public dissatisfaction with the marriage registration service through SIMKAH at the KUA, Kajoran District. SIMKAH is a government policy implemented at the Office of Religious Affairs that can assist in the process of marriage registration services. This research aims to find out how the marriage registration service is and the community's satisfaction with the service at the KUA Kajoran District. The research method used is qualitative descriptive research. The data collection techniques used were interviews, observation and documentation. Research sources consisted of the Head of KUA, staff and the community. The research data was then analyzed using interactive model analysis techniques. The research results show that (1) Marriage registration services at the Kajoran District KUA are still not optimal, so some people are unsatisfied with the services. (2) Marriage registration service products such as marriage books are given late. (3) several problems hamper marriage registration services through SIMKAH, such as lack of human resources, lack of science and technology knowledge from some Islamic religious counsellors, inadequate facilities and infrastructure, and internet network problems.